Check the Physical Development and Physical Fitness of Children in Preschool Educational Institutions (Eurasian Journal of Learning and Academic Teaching, 2023)
According to the conducted pedagogical observations, physical education lessons are held in the music room in many kindergartens. Such rooms are decorated with ageappropriate sports equipment in some kindergartens. But most kindergartens use small sports equipment (flags, bowling balls, cubes , hoops, sticks, etc.), but some kindergartens do not have them. Even if the kindergartens have basic sports fields, they are sufficient undecorated (health center, running tracks, jumping, throwing areas, etc.).